Phenotypic change in trigeminal ganglion neurons associated with satellite cell activation via extracellular signal‐regulated kinase phosphorylation is involved in lingual neuropathic pain. (4th September 2017) - Mikuzuki, Lou; Saito, Hiroto; Katagiri, Ayano; Okada, Shinji; Sugawara, Shiori; Kubo, Asako; Ohara, Kinuyo; Lee, Jun; Toyofuku, Akira; Iwata, Koichi
Abstract: Iatrogenic trigeminal nerve injuries remain a common and complex clinical problem. Satellite glial cell (SGC) activation, associated phosphorylation of extracellular signal‐regulated kinase (ERK), and neuropeptide expression in the trigeminal ganglion (TG) are known to be involved in trigeminal neuropathic pain related to trigeminal nerve injury. However, the involvement of these molecules in orofacial neuropathic pain mechanisms is still unknown. Phosphorylation of ERK1/2 in lingual nerve crush (LNC) rats was observed in SGCs. To evaluate the role of neuron–SGC interactions under neuropathic pain, calcitonin gene‐related peptide (CGRP)‐immunoreactive (IR), phosphorylated ERK1/2 (pERK1/2)‐IR and glial fibrillary acidic protein (GFAP)‐IR cells in the TG were studied in LNC rats. The number of CGRP‐IR neurons and neurons encircled with pERK1/2‐IR SGCs was significantly larger in LNC rats compared with sham rats. The percentage of large‐sized CGRP‐IR neurons was significantly higher in LNC rats. The number of CGRP‐IR neurons, neurons encircled with pERK1/2‐IR SGCs, and neurons encircled with GFAP‐IR SGCs was decreased following CGRP receptor blocker CGRP8‐37 or mitogen‐activated protein kinase/ERK kinase 1 inhibitor PD98059 administration into the TG after LNC. Reduced thresholds to mechanical and heat stimulation to the tongue in LNC rats were also significantly recovered following CGRP8‐37 or PD98059 administration. The present findings suggest that CGRP released from TG neurons activates SGCs through ERK1/2 phosphorylation and TG neuronal activity is enhanced, resulting in the tongue hypersensitivity associated with lingual nerve injury. The phenotypic switching of large myelinated TG neurons expressing CGRP may account for the pathogenesis of tongue neuropathic pain. Abstract : Phenotypic switching occurs in large‐size TG neurons expressing CGRP immuno‐products after lingual nerve crush. CGRP released from both small and large‐size TG neurons activates not only neurons but also SGCs via ERK phosphorylation, resulting in the enhancement of the TG neuronal excitability. The neuron–glia signaling mediated by phenotypic switching of CGRP‐IR TG neurons and activation of SGCs through ERK phosphorylation are likely to play a pivotal role underlying lingual neuropathic pain.